Etiology of community-acquired pneumonia in hospitalized school-age children: evidence for high prevalence of viral infections - Tsolia, M. N.; Psarras, S.; Bossios, A.; Audi, H.; Paldanius, M.; Gourgiotis, D.; Kallergi, K.; Kafetzis, D. A.; Constantopoulos, A.; Papadopoulos, N. G. (Clin Infect Dis, 2004)
Community-acquired pneumonia (CAP) in young children is most commonly associated with viral infections; however, the role of viruses in CAP of school-age children is still inconclusive.|Seventy-five school-age children hospitalized with CAP were prospectively evaluated for the presence of viral and bacterial pathogens. Nasopharyngeal washes were examined by polymerase chain reaction for viruses and atypical bacteria. Antibody assays to detect bacterial pathogens in acute-phase and convalescent-phase serum samples were also performed.|A viral infection was identified in 65% of cases. Rhinovirus RNA was detected in 45% of patients; infection with another virus occurred in 31%. The most common bacterial pathogen was Mycoplasma pneumoniae, which was diagnosed in 35% of cases. Chlamydia pneumoniae DNA was not detected in any patient; results of serological tests were positive in only 2 patients (3%). Mixed infections were documented in 35% of patients, and the majority were a viral-bacterial combination.|The high prevalence of viral and mixed viral-bacterial infections supports the notion that the presence of a virus, acting either as a direct or an indirect pathogen, may be the rule rather than the exception in the development of CAP in school-age children requiring hospitalization.
Keywords: Adolescent Child Child; Bacterial Pneumonia; Hospitalized Child; Mycoplasma Pneumonia; Preschool Chlamydophila Infections Chlamydophila pneumoniae Community-Acquired Infections Female Humans Male Mycoplasma pneumoniae Picornaviridae Infections Pneumonia; Viral Prevalence RNA; Viral Rhinovirus